2014
DOI: 10.1007/s00417-014-2732-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, microbial profiles and prognosis of microbial keratitis-associated endophthalmitis in high-risk eyes

Abstract: MK-associated endophthalmitis is a serious ocular condition occurring more frequently in elderly populations, and those with long standing severe pre-existing ocular disease. Visual outcomes are poor, often requiring evisceration/enucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
50
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 28 publications
12
50
4
2
Order By: Relevance
“…Previous large series of P. aeruginosa endophthalmitis have demonstrated a no light perception outcome in 68% to 82% of cases. 11,12,18 Anatomical outcomes were also poor; the enucleation rate in this study was 42%, slightly better than the previously reported rate of 50% to 82% observed in those other large series. 11,12,18 P. aeruginosa may cause devastating functional and anatomical outcomes secondary to the nature of its intrinsic enzymes.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Previous large series of P. aeruginosa endophthalmitis have demonstrated a no light perception outcome in 68% to 82% of cases. 11,12,18 Anatomical outcomes were also poor; the enucleation rate in this study was 42%, slightly better than the previously reported rate of 50% to 82% observed in those other large series. 11,12,18 P. aeruginosa may cause devastating functional and anatomical outcomes secondary to the nature of its intrinsic enzymes.…”
Section: Discussioncontrasting
confidence: 79%
“…11 Recently, there have been reports of multidrugresistant P. aeruginosa endophthalmitis. [15][16][17][18] Previous studies have not demonstrated the antibiotic minimal inhibitory concentrations for 90% (MIC 90) of P. aeruginosa isolates in endophthalmitis cases.…”
mentioning
confidence: 99%
“…O’Neill et al . found that among 37 patients with microbial keratitis-associated endophthalmitis, 16 (43.3%) were eviscerated or enucleated as primary treatment, and 23 (62.2%) subsequently required evisceration or enucleation7. Scott IU et al .…”
Section: Discussionmentioning
confidence: 99%
“…found that 3 (21.4%) out of 14 patients with corneal ulcer underwent evisceration or enucleation8. The risk factors for the progression from keratitis to endophthalmitis included: delayed diagnosis and treatment of microbial keratitis, the use of topical steroid, trauma, contact lens use and previous ocular surgical history78910111213141516171819. In our study, 65.2% of corneal ulcer-related endophthalmitis required enucleation or evisceration which was higher than most previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial keratitis is a sight threatening disorder associated with multiple risk factors, including use of extended wear soft contact lenses, 1 ocular surface disease, 2 ocular surgery, 3 immunosuppression, 4,5 and traumatic ocular surface accidents, particularly prevalent in developing countries. 6,7 Among pathogens, the Gram-negative bacterium, Pseudomonas aeruginosa , remains a leading cause of contact lens–induced microbial keratitis, 8 and infections result in ocular pain, stromal destruction, corneal thinning, and/or perforation, leading to vision loss, if untreated.…”
mentioning
confidence: 99%